A psychometric assessment of Disturbances in Self-Organization symptom indicators for ICD-11 Complex PTSD using the International Trauma Questionnaire. Issue 1 (1st January 2018) - Shevlin, Mark; Hyland, Philip; Roberts, Neil P.; Bisson, Jonathan I.; Brewin, Chris R; Cloitre, Marylene
ABSTRACT: Background : Two 'sibling disorders' have been proposed for the 11 th version of the International Classification of Diseases (ICD-11): Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD). To date, no research has attempted to identify the optimal symptom indicators for the 'Disturbances in Self-Organization' (DSO) symptom cluster. Objective : The aim of the current study was to assess the psychometric performance of scores of 16 potential DSO symptom indicators from the International Trauma Questionnaire (ITQ). Criteria relating to score variability and their ability to discriminate were employed. Method : Participants ( N  = 1839) were a nationally representative household sample of non-institutionalized adults currently residing in the US. Item scores from the ITQ were examined in relation to basic criteria associated with interpretability, variability, homogeneity, and association with functional impairment. The performance of the DSO symptoms was also assessed using 1- and 2-parameter item response theory (IRT) models. Results : The distribution of responses for all DSO indicators met the criteria associated with interpretability, variability, homogeneity, and association with functional impairment. The 1-parameter graded response model was considered the best model and indicated that each set of indictors performed very similarly. Conclusions : The ITQ contains 16 DSO symptom indicators and they perform well in measuring their respective symptom cluster. There was no evidence that particular indicators were 'better' than others, and it was concluded that the indicators are essentially interchangeable.